A Study of Code Switching and Code Mixing on Youtube Talk Show Curhat Bang Denny Sumargo with Cinta Laura - Nurhayati S. (ITScience (Information Technology and Science), 2021)
Wardhaugh (2006:1) in his introduction stating that when two or more people communicate with each other in speech, they employ a code as the system of communication. The study was conducted to elaborate on the types and the purposes of code-switching and code-mixing with their occurrence. The method of this study used qualitative descriptive to analyze the data. The data was taken from the talk show ‘CURHAT BANG Denny Sumargo’ with Cinta Laura on Youtube. The results of this study show that the most dominant type of code-switching and mixing is intrasentential and insertion (76,5 % and 56, 58 %). Moreover, 9 (nine) purposes of using code-switching and code-mixing are found in this study and the most frequent one is the intention to clarify (32,9 %). This study also showed that Cinta Laura as a multilingual person is the one who is more prominent in switching and mixing the codes from Indonesian into English.